Elaboration of a policy on electronic document management: the case of the Fundación Estatal para la Formación en el Empleo File - Morena de Diago, Beatriz (Revista General de Información y Documentación, 2021)
A policy on electronic document management is of key importance in the advance to electronic administration, with guidance or guidelines for the creation and management of genuine and reliable documents, available over time, according to the functions and activities of a organization. This article reflects on the essential characteristics and recommendations for defining policies on electronic document management based on the development of the electronic document management Policy of the Fundación Estatal para la Formación en el Empleo.
Keywords: Policy on electronic document management; electronic document; Electronic file; Document management; e-Administration; Fundae; NTI